A complex phosphodiesterase system controls β-adrenoceptor signalling in cardiomyocytes. (21st July 2006) - Mongillo, M.; Zaccolo, M.
Abstract : β-Adrenergic signalling mediates the positive inotropic effect of catecholamines on cardiomyocytes, mainly through cAMP generation and subsequent activation of PKA (protein kinase A). Given the large diversity of PKA targets within cardiac cells, a precisely regulated and confined activity of such signalling pathways is essential for the specificity of response. PDEs (phosphodiesterases) constitute the only cAMP-degrading mechanism and are expressed in the cardiomyocyte in at least 5 family variants. Each PDE family is characterized by unique functional properties and contributes to a cAMP-degrading system enabling the modulation of PKA activity in a stimulus-dependent fashion.